Economic Valuation Of Mangrove Carbon Stock In Umbrella Island, Banyuasin Regency, South Sumatra Province - Septi Hermialingga; Agung Kurniawan; Nancy Eka Manurung (Journal Of Social Science (JoSS), 2023)
This study aims to conduct an economic valuation of mangrove carbon stocks found on Payung Island, Banyuasin Regency, South Sumatra Province. Mangroves are coastal ecosystems that play an important role in storing carbon and providing ecological and socio-economic benefits to local communities. The research method used is a field survey and analysis of the latest data on carbon content in mangrove ecosystems. In addition, interviews were also conducted with relevant stakeholders to understand the economic benefits generated from mangrove ecosystems, such as income from the fisheries sector, tourism, and conservation efforts. The results of this study are expected to provide information about the economic value of mangrove carbon stocks on Payung Island. The implications of this research are expected to be used as a basis for decision making related to mangrove ecosystem management and preservation. In addition, this research can also provide a better understanding of the importance of mangrove conservation as a valuable natural resource, both in terms of environment and economy